50 Patient insights of fatigue in systemic lupus erythematosus and content validation of the FACIT-Fatigue. (April 2019) - Park, Josephine; Raymond, Kimberly; White, Michelle; Joshi, Ashish
Abstract : Background: Fatigue is a predominant symptom experienced by patients with systemic lupus erythematosus (SLE) and is known to have a significant burden on daily life. To capture the impact of fatigue on patients with SLE accurately and effectively, a validated fatigue measure must be utilized. This study (GSK Study 209226) evaluated the content validity of the Functional Assessment of Chronic Illness Therapy (FACIT) Fatigue instrument to investigate whether this instrument is a valid and appropriate measure of fatigue within this population and to understand SLE related fatigue better. Methods: Fifteen 90 min qualitative interviews were conducted by telephone in July 2018 using concept elicitation (CE) and cognitive debriefing techniques. Participants were asked to share their experiences of SLE symptoms, focusing on fatigue and its impact on their daily life. Participants were then asked to evaluate how well they interpreted and understood the questions and response options of the FACIT-Fatigue instrument, along with the appropriateness and relevance of the items, response scales and recall periods. Patients were eligible to participate if they were 18 years of age, had a self reported doctor diagnosis of SLE with persistent symptoms for 6 months or 1 SLE flare in the previous 12 months despite treatment with steroids/immunosuppressants. Participants were positive for antinuclear antibody or antidouble-stranded deoxyribonucleic acid and spoke fluent English. Results: The sample (female, n=13/15) was diverse by age (mean [standard deviation] age 52.1 [13.1] years), race and ethnicity, severity, and time since diagnosis. Results of the CE segment of the interview are displayed in the table. Eleven participants (73.3%) reported fatigue as their most bothersome symptom. Significant impacts of fatigue were described in relation to emotional (n=10), social (n=6), and physical (n=5) functions, as well as role difficulties (n=4) and struggles with activities of daily living (n=4). Qualitative analyses revealed that all FACIT Fatigue items map directly onto concepts spontaneously mentioned by participants during the interviews. All participants reported that the FACIT Fatigue items were easily understood, relevant, appropriate, and concise, and captured the most important concepts related to fatigue in SLE. Conclusions: The interviews demonstrated fatigue to be a central concern to patients with SLE and supported the content validity of the FACIT-Fatigue instrument as an appropriate and interpretable assessment of fatigue for this population. This study provides valuable insights into the experiences of patients with SLE and, specifically, the impact of fatigue on these patients. Funding Source(s): Study funded by GlaxoSmithKline.